Impact of an antimicrobial stewardship program in the antimicrobial-resistant and prevalence of clostridioides difficile infection and amount of antimicrobial consumed in cancer patients - Masoud Mardani; Sara Abolghasemi; Shiva Shabani (BMC Research Notes, 2020)
Abstract Objective The The impact of a hospital antimicrobial stewardship was determined on antimicrobial-resistant, Clostridioides difficile rates and the amount of antimicrobial consumed in cancer patients.The intervention effects of antimicrobial stewardship (ASP) plans in 2017–2018 and 2018–2019 were respectively evaluated among hematology/oncology and bone marrow transplant patients in Ayatollah Taleghani University Hospital, Tehran, Iran. In this interventional quasi-experimental study, the ASP repository was utilized to capture four survey questions encompassed in these immunocompromised patients: amount of antibiotics (meropenem and vancomycin) consumption gr-year, the number of positive Clostridioides difficile infection and multidrug-resistant positive cases in blood cultures. Results The number of MDR cases in the periods of 2017–2018 and 2018–2019 were 145 and 75, respectively (p = 0.011). A significant reduction in all positive blood cultures from 2017–2018 to 2018–2019 was found (p = 0.001). 574 patients admitted to our hospital in these periods of 2017- 2018 and 2018- 2019were assessed for MPM and VMN use. The amounts of MPM prescriptions in 2018–2019 was significantly decreased from 22464 to 17262 g (p = 0.043). The significant reduction in antibiotic consumption, MDR organisms, and CDI can highly promote patients’ health and decreasing medical costs and long-term defects for patients.